Excessive versus Physiologically Relevant Levels of Retinoic Acid in Embryonic Stem Cell Differentiation. (23rd May 2014) - Sheikh, Bilal N.; Downer, Natalie L.; Kueh, Andrew J.; Thomas, Tim; Voss, Anne K.
Abstract: Over the past two decades, embryonic stem cells (ESCs) have been established as a valuable system to study the complex molecular events that underlie the collinear activation of Hox genes during development. When ESCs are induced to differentiate in response to retinoic acid (RA), Hox genes are transcriptionally activated in their chromosomal order, with the most 3′ Hox genes activated first, sequentially followed by more 5′ Hox genes. In contrast to the low levels of RA detected during gastrulation (∼33 nM), a time when Hox genes are induced during embryonic development, high levels of RA are used to study Hox gene activation in ESCs in vitro (1–10 µM). This compelled us to compare RA-induced ESC differentiation in vitro with Hox gene activation in vivo. In this study, we show that treatment of ESCs for 2 days with RA best mimics activation of Hox genes during embryonic development. Furthermore, we show that defects in Hox gene expression known to occur in embryos lacking the histone acetyltransferase MOZ (also called MYST3 or KAT6A) were masked in Moz -deficient ESCs when excessive RA (0.5–5 µM) was used. The role of MOZ in Hox gene activation was only evident when ESCs were differentiated at low concentrations of RA, namely 20 nM, which is similar to RA levels in vivo. Our results demonstrate that using RA at physiologically relevant levels to study the activation of Hox genes, more accurately reflects the molecular events during the early phase of Hox gene activation in vivo. Stem Cells 2014;32:1451–1458